GAYA BAHASA PADA LIRIK LAGU NOAH DALAM ALBUM KETERKAITAN KETERIKATAN - Fahrul Rozi; Dudung Burhanuddin; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study was to look at the style of language contained in the lyrics of the song Noah album Keterkaitan Keterikatan after 7 years of not releasing a new album. The research method used is descriptive qualitative with data collection techniques observing and taking notes. Data analysis techniques used start from identifying, classifying, analyzing, explaining, and concluding which is better known as descriptive analysis. As a result, from 47 datums, 4 language styles were found, namely repetition language style; 1) alliteration 2) assonance 3) epizeuksis 4) anaphora, comparative figurative language; 1) personification, conflicting language style; 1) hyperbole 2) climax, and linking language style; 1) euphemism. The writer concludes that the lyrics of Noah's album, Keterkaitan Keterikatan, are dominant in the language style of comparison and repetition. This shows the sadness about love which is emphasized in the language style of repetition and is illustrated through inanimate objects with the style of comparison.Keywords: Language Style, Song Lyrics, Noah